2018
DOI: 10.3390/w10121853
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Gaps in Environmental Water Policy Issues across Five Mediterranean Freshwater Protected Areas

Abstract: The increasing pressure on water resources in Europe’s broader area led member states to take measures and adopt a common legislative “umbrella” of directives to protect them. The aim of this research is to investigate practicing deficiencies, information lacks and distances from optimal status as set by the Water Framework Directive and supporting water uses. This contributes to the improvement of the efficiency and harmonization of all environmental goals especially when management of Protected Areas is addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The Water Framework Directive (WFD) 2000/60/EC aims at protecting all water systems in the European Union's territory. Based on the WFD guidelines set regarding water systems, a study to identify environmental policy gaps in Mediterranean national parks (hydro-ecosystems) was done [7]. Using gap analysis, the results confirmed that human pressures altered national parks, and in particular, human pressures and eutrophication are the main factors.…”
Section: Water Resources and Irrigation Systemsmentioning
confidence: 88%
See 1 more Smart Citation
“…The Water Framework Directive (WFD) 2000/60/EC aims at protecting all water systems in the European Union's territory. Based on the WFD guidelines set regarding water systems, a study to identify environmental policy gaps in Mediterranean national parks (hydro-ecosystems) was done [7]. Using gap analysis, the results confirmed that human pressures altered national parks, and in particular, human pressures and eutrophication are the main factors.…”
Section: Water Resources and Irrigation Systemsmentioning
confidence: 88%
“…To solve the problem of optimum allocation of water and to locate one or more new reservoirs in a river-with-reservoirs system, a MILP model is used [13]. Additionally, management measures are assessed in Mediterranean national parks showing that there are inconsistencies with the guidelines set by the WFD (such as in monitoring water systems) [7]. The causes are mainly human interventions and eutrophication causing pollution.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of monitoring gaps is also found in Latinopoulos et al [18]. In this paper, five case studies in the Mediterranean area are selected and a GA is performed on policy factors so as to improve monitoring, management, and networking practices.…”
Section: Scientific Litmentioning
confidence: 93%
“…Latinopoulos et al [18] GA of management and monitoring practices, water and quality pressures. Lehmann et al [19] GA of existing regional observation systems.…”
Section: Scientific Litmentioning
confidence: 99%